Management of Aortic Stenosis in Patient Known Case of End-stage Renal Disease with Anuria on Hemodialysis - Sonia; Neetu Kataria; V. R. Vijay; Kusum Kumari; Sudhir Kumar Shahi (Journal of Applied Sciences and Clinical Practice)
Cardiovascular disease affects more than 50% of individuals receiving dialysis. Cardiac issues affect about half of dialysis patients with end-stage renal disease (ESRD). The most prevalent valvular pathology among chronic renal disease patients receiving hemodialysis is aortic valve dysfunction. This case report presented very high-risk surgery in anuria patients with favorable outcomes. Forty-six-year-old male was a known case of ESRD on hemodialysis (HD) for the last 3–4 years under the treatment of a nephrologist. He is admitted with complaints of breathlessness at rest, weakness with lethargy, occasional chest pain, and anuria. In view of his symptomatology two-dimensional echocardiography which revealed severe aortic stenosis. No Foley catheterization was done in view of anuria during surgery. The #21 mm bileaflet mechanical aortic valve prosthesis was implanted. Intraoperative hemofilter was used to manage the fluid balance (3 L ultrafiltration done during cardiopulmonary bypass). Presurgery HD used to be of relatively prolonged duration and without getting required ultrafiltration. After surgical intervention, dialysis was done smoothly, without any episodes of hypotension and HD duration is shortened.